Survival study of escherichia coli o157:h7 in aquatic system of Bangladesh - Jahid, Iqbal Kabir; Azad, Taslima; Rahman, Mohammed Ziaur; Begum, Anowara; Khan, Sirajul Islam; Akhter, Humaira (Dhaka University Journal of Biological Sciences, 2011)
The survival pattern of Escherichia coli O157:H7 was observed in laboratory microcosm with different sources of surface and drinking water using the green fluorescent protein (GFP) as a genetic marker. The water quality was monitored on the basis of bacteriological and physico?chemical parameters. The untreated and filtered water were inoculated with the genetically transformed E. coli O157:H7. The survival pattern was determined by drop plate method observing the green fluorescence of the E. coli O157:H7 colonies under UV light. The survival of E. coli O157:H7 decreased in most of the untreated saline and waste water and higher survival was observed in pond and tap water. The E. coli O157:H7 survived more than 23 days in tap and pond water and less than 20 days in sea, estuarine and waste water. The fluorescent microscopic findings revealed the VBNC state of E. coli O157:H7. The study conclusively proved that the better survival of E. coli O157: H7 depends on the quality of water. Key words: E. coli O157:H7; Aquatic system; Survival study DOI: http://dx.doi.org/10.3329/dujbs.v19i2.8964 DUJBS 2010; 19(2): 195-201